2021
DOI: 10.1021/acsomega.1c04109
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Characterization of Kurarinone as a Dopamine D1A Receptor Antagonist and D2L and D4 Receptor Agonist

Abstract: Alterations in the expression and/or activity of brain G-protein-coupled receptors (GPCRs) such as dopamine D 1 R, D 2L R, D 3 R, and D 4 R, vasopressin V 1A R, and serotonin 5-HT 1A R are noted in various neurodegenerative diseases (NDDs). Since studies have indicated that flavonoids can target brain GPCRs and provide neuroprotection via inhibition of monoamine oxidases (hM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Additionally, they found that it is an MAO-A inhibitor with an IC 50 value of 8.57 ± 0.47 µM [49]. Likewise, a prenylated flavanone, kurarinone, was also found to be a D 1A R antagonist and a D 2L and D 4 agonist [50]. 3 ,4 ,7-Trihydroxyflavone (1) decreases NO production and exerts an anti-neuroinflammatory effect through the inhibition of the JNK-STAT1 pathway in microglia [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they found that it is an MAO-A inhibitor with an IC 50 value of 8.57 ± 0.47 µM [49]. Likewise, a prenylated flavanone, kurarinone, was also found to be a D 1A R antagonist and a D 2L and D 4 agonist [50]. 3 ,4 ,7-Trihydroxyflavone (1) decreases NO production and exerts an anti-neuroinflammatory effect through the inhibition of the JNK-STAT1 pathway in microglia [51].…”
Section: Discussionmentioning
confidence: 99%
“…a,b % stimulation and % inhibition of control agonist response at 100 µM of compounds, respectively, were calculated from a log dose inhibition curve and expressed as mean ± SD of triplicate experiments. c EC50 (nM) values of standard agonists (D 1 , D 2L , D 3 , and D 4.4 : dopamine, 5-HT 1A : serotonin). d IC 50 (nM) values of standard antagonists (D 1 : SCH-23390, D 2L : butaclamol, D 3 : (+)-butaclamol, D 4.4 : clozapine, and 5-HT 1A : (S)-WAY-100635).…”
mentioning
confidence: 99%
“…Kurarinone ( 94 ) is an abundant lavandulylated flavonoid isolated from the perennial shrub Sophora flavescens (Fabaceae) . Known as Kushen, the dried roots of S. flavescens are used in traditional Chinese medicine for the treatment of cancer and inflammatory diseases .…”
Section: Miscellaneous Dopamine Receptor-targeted Natural Productsmentioning
confidence: 99%
“…522 could bind well to dopamine receptor subtypes, unfolding antagonist behavior on D 1 R (IC 50 : 42.1 µ M) and agonist effects on D2LR and D4R (EC 50 22.4 and 71.3 µ M, respectively). 522 suppressed hMAO isoenzymes in a modest and nonspecific manner (Prajapati et al 2021 ). 579 acted at GABA A receptors in the hippocampal nerve terminals to downregulate the Ca 2+ influx by N- and P/Q-type Ca 2+ channels, which subsequently suppressed the Ca 2+ -calmodulin/PKA cascade to reduce the evoked glutamate release.…”
Section: Prenylated Flavonoids With Anti-inflammatory Activitymentioning
confidence: 99%